Self-Care Experiences of Empty-Nest Elderly Living With Type 2 Diabetes Mellitus: A Qualitative Study From China - Lv, Xiaoyan; Yu, Doris S. F.; Cao, Yingjuan; Xia, Jinghua (Frontiers in Endocrinology, 2021)
Background: The number of type 2 diabetes mellitus (DM) cases among empty-nest elderly increases with increasing aging in China. Self-care plays an important role in preventing and reducing adverse outcomes of diabetes; however, few studies focus on self-care experiences of empty-nest elderly with type 2 DM. Objective: To explore self-care experiences for a chronic disease among empty-nest elderly patients with type 2 DM in mainland China. Methods: A descriptive phenomenological design was used in this study. Semi-structured interviews were conducted for 15 empty-nesters with type 2 DM Interviews were implemented in two endocrinology wards at a tertiary teaching hospital located in Shandong province, eastern of China. Results: The participants were poorly adept with monitoring their blood glucose and lacked the ability to deal with abnormal blood glucose levels. Most participants had a good relationship with medication and physical activity. Living without children was perceived as a benefit that improved dietary management, and is a disadvantage in terms of economic and emotional support and access to medical resources. Elderly empty-nesters also lacked knowledge about diabetes and paid little attention to potential complications. Conclusion: Empty-nest elderly patients with type 2 DM value medication compliance and lifestyle modification much more than blood glucose monitoring, complication prevention, and coping with negative emotions. Friends and spouses play indispensable roles in patients’ self-care motivation and maintenance. Diabetes education on self-care, access to medical resources, and social support is needed for better diabetes management.